PEMANFAATAN DAUN SINGKONG (Manihot utilissima) TUA SEBAGAI PAKAN IKAN GURAMI (Osphronemus gouramy. Lac) - Syahrizal Syahrizal; Muarofah Ghofur; Fakhrurrozi Fakhrurrozi (Jurnal Ilmiah Universitas Batanghari Jambi, 2013)
This experiment aims to study the response of carp (Ospronemus gouramy Lac.) Mean ± 13 grams of cassava leaves early against granting soaked (B), boiled (C), fermented (D), and natural cassava leaves (as a control) were be rearing in semi indorHaving analyzed with ANOVA and LSD (Least Significant Difference) results showed that the highest growth resulting from the treatment of fermented (D) is equal to 30.73 grams and growth absolut 20.67 grams for 40 days were significantly different (P <0, 5). While the survival of the fish ranged 80.00% -93.33% and the best level in feed fermented cassava leaves 93.33%.Kata kunci: Daun singkong, Fermentasi dan ikan Gurami